The chemical and antioxidant stability of isolated low molecular weight phlorotannins. (15th April 2017) - Kirke, D.A.; Smyth, T.J.; Rai, D.K.; Kenny, O.; Stengel, D.B.
Highlights: Low molecular weight phlorotannins show promising potential for food applications. Polymeric fractions demonstrated high degree of stability and antioxidant activity. Degradation occurred after 8 weeks but only in aqueous samples stored at 50 °C. Continuous exposure to oxygen led to an isomeric increase in aqueous samples. Abstract: Due to their high anti-oxidant activity, phlorotannins represent potential natural alternatives to synthetic preservatives currently used within the food industry. However, their successful integration into food products requires research into their chemical integrity, particularly when selecting appropriate storage conditions. Subsequently, this study aims to investigate the stability of low molecular weight phlorotannin fractions from Fucus vesiculosus (L.). Powder and aqueous fractions were stored under five different conditions for 10 weeks. Phlorotannin stability was determined using Q-ToF-MS and UPLC-TQD-MS/MS and a DPPH assay. After 10 weeks of storage, fractions suspended in an aqueous matrix underwent oxidation when exposed to continuous atmospheric oxygen and thermal degradation when exposed to a constant temperature of 50 °C, resulting in decreases in radical scavenging activity (p < 0.001). Phlorotannins remained stable under all other storage conditions. This study highlights phlorotannins as highly stable polymers, under certain storage conditions, with an excellent capacity for scavenging radicals.